Structural and molecular analysis of a protective epitope of Lyme disease antigen OspA and antibody interactions. Issue 5 (16th November 2016) - Shandilya, Shivender; Kurt Yilmaz, Nese; Sadowski, Andrew; Monir, Ejemel; Schiller, Zachary A.; Thomas, William D.; Klempner, Mark S.; Schiffer, Celia A.; Wang, Yang
Abstract: The murine monoclonal antibody LA‐2 recognizes a clinically protective epitope on outer surface protein (OspA) of Borrelia burgdorferi, the causative agent of Lyme disease in North America. Human antibody equivalence to LA‐2 is the best serologic correlate of protective antibody responses following OspA vaccination. Understanding the structural and functional basis of the LA‐2 protective epitope is important for developing OspA‐based vaccines and discovering prophylactic antibodies against Lyme disease. Here, we present a detailed structure‐based analysis of the LA‐2/OspA interaction interface and identification of residues mediating antibody recognition. Mutations were introduced into both OspA and LA‐2 on the basis of computational predictions on the crystal structure of the complex and experimentally tested for in vitro binding and borreliacidal activity. We find that Y32 and H49 on the LA‐2 light chain, N52 on the LA‐2 heavy chain and residues A208, N228 and N251 on OspA were the key constituents of OspA/LA‐2 interface. These results reveal specific residues that may be exploited to modulate recognition of the protective epitope of OspA and have implications for developing prophylactic passive antibodies. Abstract : The interface between outer surface protein (OspA) of Borrelia burgdorferi, the causative agent of Lyme disease in North America, and the monoclonal antibody LA‐2 was interrogated by mutational analysis. Mutations were introduced into both OspA and LA‐2, guided by computational predictions on the crystal structure of the complex, and experimentally tested for in‐vitro binding and borreliacidal activity. The results reveal specific residues that may be exploited to modulate recognition of the protective epitope of OspA and have implications for developing prophylactic passive antibodies against Lyme disease.